Engineers Who Become Entrepreneurs; How to Study Them through Phenomenology - Farsi, Jahangir Yadollahi; Baradaran, Mohammad Sadegh; Hejazi, Seyed Reza; Akbari, Morteza (International Journal of Economics and Financial Issues, 2018)
The role of new technological businesses in economic development and social transformation is undeniable. The study of engineer-entrepreneur as the heart of these businesses is one of the main research areas in the field of entrepreneurship. Engineer-entrepreneur is defined as an engineer establishes a new technology business and manage it based on development of advanced technology and commercialization. Designing a clear methodology for study of engineer-entrepreneurs can be effective not only in creating and growing the businesses of entrepreneur-entrepreneurs, but also in providing better educating entrepreneurship to engineers. So this article systematically reviews the indexed articles in the Scopus database related to the usage of phenomenology in entrepreneurship. The analysis of 78 related articles indicates that the process of applying phenomenological method for study of entrepreneurs is growing. In response to the question of how phenomenology is applied, the results of the reviewed articles were described in seven sections, including the defining of subject, the selection of phenomenological procedure, the selection of participants and sampling, data collection, Analysis, validation, and presentation. This phenomenological method for study of engineer-entrepreneurs is illustrated through a worked example of competency for being engineer-entrepreneur. Keywords: Engineer, Entrepreneur, Phenomenology, Methodology, competency JEL Classifications: L26, O15